Integrated pest management in vegetable production: a guide for extension workers in West Africa - Atcha-Ahowé, C.; Baimey, H.; Godonou, I.; Goergen, Georg E.; James, B.; Sikirou, R.; Toko, M. (International Institute of Tropical Agriculture, 2010)
This guide has been produced by the International Institute of Tropical Agriculture (IITA) and Institut National des Recherches Agricoles du Bénin (INRAB), Cotonou, Benin, with support from the CGIAR Systemwide Program on Integrated Pest Management (SP-IPM), to improve the quality and usefulness of pest management research. This publication was part funded by the ACP-EU Technical Centre for Agricultural and Rural Cooperation (CTA).